The Causes and Consequences of miR-503 Dysregulation and Its Impact on Cardiovascular Disease and Cancer - He, Yanjing; Cai, Yin; Pai, Pearl Mingchu; Ren, Xinling; Xia, Zhengyuan (Frontiers in Pharmacology, 2021)
microRNAs (miRNAs or miRs) are short, non-coding RNAs that regulate gene expression by mRNA degradation or translational repression. Accumulated studies have demonstrated that miRNAs participate in various biological processes including cell differentiation, proliferation, apoptosis, metabolism and development, and the dysregulation of miRNAs expression are involved in different human diseases, such as neurological, cardiovascular disease and cancer. microRNA-503 (miR-503), one member of miR-16 family, has been studied widely in cardiovascular disease and cancer. In this review, we summarize and discuss the studies of miR-503 in vitro and in vivo, and how miR-503 regulates gene expression from different aspects of pathological processes of diseases, including carcinogenesis, angiogenesis, tissue fibrosis and oxidative stress; We will also discuss the mechanisms of dysregulation of miR-503, and whether miR-503 could be applied as a diagnostic marker or therapeutic target in cardiovascular disease or cancer.